PENERAPAN KARTU IDENTITAS ANAK DI KABUPATEN SEKADAU - Syamsudin, Martinus; Krisyanti Trinasari, Angelina (FOKUS : Publikasi Ilmiah untuk Mahasiswa, Staf Pengajar dan Alumni Universitas Kapuas Sintang., 2025)
in Sekadau Regency. The objectives of this study are to understand, describe, and analyze the implementation of Child Identity Cards in Sekadau Regency. This research method used descriptive research. The subjects were the Head of the Civil Registration Service, the Head of the Population and Civil Registration Services Division, and several community members who received services. The research techniques used for data collection included observation, interviews, and documentation studies, with data analysis using qualitative descriptive analysis. The results of the study indicate that information dissemination and outreach related to the Child Identity Card Program have been implemented, with partnerships established with other institutions in education and health, and outreach efforts at the village level, as well as the use of social media. Resources are sufficient, supported by legal instruments as a basis for implementation, human resources, facilities, infrastructure, and a budget provided by the government, enabling services to be implemented in the Child Identity Card Program. Dispositions have been implemented, with the implementation of core tasks and functions, particularly in the field of population registration services, as a commitment to issuing Child Identity Cards. However, community support is still needed. The researcher recommends the following: Information dissemination and outreach related to the Child Identity Card Program should be continuously improved, particularly through social media and websites. Resources need to be optimized as a basis for service delivery in the implementation of the Child Identity Card Program in Sekadau Regency. The disposition for continued optimization requires support from discipline and active community cooperation for the success of the government program.